Cerebral microbleeds in traumatic brain injury: their impact on white matter integrity assessed by diffusion MRI - Bognár, Dávid; Petneházy, Zalán; Laár, Péter; Dóczi, Tamás; Schwarcz, Attila; Környei, Bálint S.; Tóth, Arnold (Frontiers in Neurology, 2025)
IntroductionTraumatic Brain Injury (TBI) often leads to lasting cognitive and functional deficits, with Traumatic Axonal Injury (TAI) being a significant prognostic factor. This study investigated white matter microstructural changes in moderate-to-severe TBI, focusing on the presence and number of cerebral microbleeds (MBs) using diffusion tensor imaging (DTI).Materials and methods51 participants were recruited and categorized into three groups: 17 controls, 17 TBI patients with MBs (MBP), and 17 TBI patients without MBs (MBN). Age matching was applied to minimize confounding effects. MRI scans were acquired using a 3 T Siemens MAGNETOM Prisma scanner, and DTI data were preprocessed using FSL software. Whole white matter and corpus callosum masks were reconstructed using FreeSurfer, while tractography-based methods were implemented with FSL. Fractional anisotropy (FA) and mean diffusivity (MD) were extracted and compared across groups. Group-level voxel-wise statistical analysis was conducted using Tract-Based Spatial Statistics (TBSS), and generalized linear models (GLiMs) were applied to assess the effects of age, sex and MB number on DTI parameters.ResultsSignificant decrease in FA (p = 0,008 − 0,042) and increases in MD (p = 0,004 − 0,016) were observed in the WM masks when comparing the MBP group with the controls. In the TBSS analysis FA (p = 0,008) and MD (p = 0,005) showed significant differences between the MBP-CON comparison, while FA (p = 0,012) and MD (p = 0,043) were significantly different between the MBP and MBN groups. Moreover, a significant FA decrease was observed in the corpus callosum when comparing the MBP and MBN groups (p = 0,007). Additionally, an increasing number of microbleeds was significantly associated with altered DTI metrics in across all white matter masks.ConclusionOur findings highlight MBs as potential markers of more extensive white matter injury in moderate-to-severe TBI. The increase in MBs suggests even greater white matter damage, indicating a progression of microstructural alterations. On a global scale, tractography enhances the sensitivity in detecting structural alterations compared to traditional segmentation techniques. Examination of central white matter areas holds significant importance in uncovering the relevance of MBs.